Pengujian Dampak Sistem Insentif Dan Orientasi Kognitif Terhadap Kinerja Kelompok: Studi Di Indonesia - Siti Muslihah; Sakina Nusarifa Tantri (Jurnal Gama Societa, 2018)
This study aims to find out individual’s performance based on their cognitive orientation towards incentive system. This study refers to a previous study (Naranjo-Gil et al., 2012) that tested similarly that the study was conducted in Indonesia which has a different culture with the previous research’s origin country. This study used case study method with college student respondent that had economics background. The results of this study revealed that some conclusions. First, individual behavior in completing tasks tends to match with their cognitive orientation. Second, there was a difference between individualism cognitive orientation when they given to team-based structure incentive system. Third, there are differences in collectivism cognitive orientation groups when they given to an individual-based structure incentive system. The most appropriate incentive system used to improve the group performance which respect to the cognitive orientation group members is the team-based incentive system.